PENGARUH SISTEM PEMBELAJARAN DAN KEPUASAN KERJA DOSEN TERHADAP KINERJA DOSEN DI STIKES KARSA HUSADA GARUT - Suliyawati, Eti (PEDAGOGIA, 2017)
Central issue in this study is teacher performance is not optimal, the researchers observed due to learning andjob satisfaction of teachers who have not been going well. On the basis of thought and consideration, theresearchers wanted to investigate further in the form of research thesis entitled "Effect of learning and teachers'job satisfaction on the performance of teachers in STIKes Karsa Husada Garut.." The method used isexplanatory survey method, ie a method that aims to test the hypothesis that has been formulated previously.Technical analysis is a statistical technique that serves to classify descriptive data, work, conclude, explain andpresent the processed results. It aims to make the pattern a causal relationship between the value of a variable toanother variable. Analysis of the data processing using path analysis (Path analisys). The results showed that theperformance of teachers affected by the learning system variables and job satisfaction of teachers, eitherpartially or simultaneously. Partially influenced by the variable performance of teachers learning system by47,2%, and influenced by teachers' job satisfaction variables of 18,8%, and the rest is influenced by othervariables. The conclusion of this research is learning and teacher job satisfaction has been empirically to giveeffect to the performance of teachers in STIKes Karsa Husada Garut, either partially or simultaneously. Theresults also found that teacher performance is also influenced by other factors academically recognized.